Genetic Diversity and Domestication Footprints of Chinese Cherry [Cerasus pseudocerasus (Lindl.) G.Don] as Revealed by Nuclear Microsatellites - Zhang, Jing; Chen, Tao; Wang, Yan; Chen, Qing; Sun, Bo; Luo, Ya; Zhang, Yong; Tang, Haoru; Wang, Xiaorong (Frontiers in Plant Science, 2018)
Chinese cherry (Cerasus pseudocerasus (Lindl.) G.Don) is a commercially important fruit crop in China, but its structure patterns and domestication history remain imprecise. To address these questions, we estimated the genetic structure and domestication history of Chinese cherry using 19 nuclear microsatellite markers and 650 representative accessions (including 118 Cerasus relatives) selected throughout their natural eco-geographical distributions. Our structure analyses detected no genetic contribution from Cerasus relatives to the evolution history of Chinese cherry. A separate genetic structure was detected in wild Chinese cherries and rough geographical structures were observed in cultivated Chinese cherries. One wild (wild Chinese cherry, WC) and two cultivated (cultivated Chinese cherry, CC1 and CC2) genetic clusters were defined. Our approximate Bayesian computation analyses supported an independent domestication history with two domestication events for CC1 and CC2, happening about 3900 and 2200 years ago, respectively. Moderate loss of genetic diversity, over thousand-year domestication bottlenecks and divergent domestication in fruit traits were also detected in cultivated Chinese cherries, which is highly correlated to long-term clonal propagation and different domestication trends and preferences. Our study is the first to comprehensively and systematically investigate the structure patterns and domestication history for Chinese cherry, providing important references for revealing the evolution and domestication history of perennial woody fruit trees.